Heiss 2015. Musa. En essay in the anthropology of the individual - Widlok, Thomas (AAeO - Afrikanistik-Aegyptologie-Online, 2017)
Heiss, Jan Patrick 2015. Musa. An essay (or experiment) in the anthropology of the individual. Berlin: Duncker & Humblot, ISBN- ISBN 9783428147816, 89,90€